Modeling of Radiative Properties of Polystyrene Foams Containing IR-Opacifiers. Issue 2 (March 2016) - Arduini, M.; Manara, J.; Vo, C.
The addition of opacifiers in foams considerably reduces the radiative thermal conductivity and consequently enhances the insulation performance of the foams. In this work two different methods were developed to calculate the spectral specific extinction coefficient of opacified extruded polystyrene (XPS) foam material. Cell morphology and thermal conductivity of two identical XPS-foams, one opacified with 3 wt% carbon black as opacifier and one without opacifier, were thoroughly characterized. The experimental results were in a good agreement with the theoretical results obtained from two different computing techniques. These methods allow a good prediction of the specific extinction coefficient of arbitrary opacified foam material.